ComplianceiwithiIron Supplement Tablet Consumption Reviewed from the Knowledgeiand Attitudes ofiPregnant Women iniPuskesmas Sungai Iyu - CHRESNANDO GINTING, JOE; Cut Nurjulianti; Karnirius Harefa; Monika Helen Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Anemia in pregnant women remains a serious problem in Indonesia because it contributes to increased morbidity and mortality rates among mothers and infants. To address this problem, the government has launched the Iron Supplement Tablet (TTD) program; however, TTD usage among children remains low. This study aims to understand the relationship between parents' knowledge and behavior and their level of compliance in consuming TTD at the Sungai Iyu Community Health Center, Bendahara District. This cross-sectional study involved 47 employees in the working area of the Sungai Iyu Community Health Center using total sampling, knowledge, attitud, and TTD consumption data, and analyzed using the Chi-Square test. The results showed that although most parents had good knowledge (46.8%) and good attitudes (52.2%), TTD consumption was still relatively low at 55.3%. There was a significant correlation between knowledge, attitudes, and compliance; therefore, education and sustainability are needed to increase TTD consumer compliance.